Validitas dan reliabilitas Skala Welas Diri pada orang tua dari anak dengan autisme di Indonesia - Ni'matuzahroh; Nafis, Alfi Yasyfizan (Konsorsium Psikologi Ilmiah Nusantara, 2024)
Having a child with autism can significantly affect parents’ sense of self-compassion, which in turn impacts their psychological well-being. In Indonesia, there is a lack of consensus among scholars regarding a standardized tool to measure self-compassion among parents of autistic children. Hence, this study aimed to validate and establish the reliability of the Indonesian version of the Self-Compassion Scale tailored for parents of autistic children. Participants in this study were 455 parents of autistic children aged 2–18 years, selected via purposive sampling. Participants were asked to complete the scale through an online platform. Confirmatory Factor Analysis (CFA) results indicated satisfactory validity (ranging from .47–.73) with 26 valid items. Moreover, the scale demonstrated adequate reliability, as indicated by Composite Reliability (CR) values ranging from .70–.80 and Variance Extracted (VE) values ranging from .32–.50. These findings confirm that the Indonesian version of the Self-Compassion Scale is a valid and reliable tool for measuring self-compassion in parents of autistic children.